Valorization and sequestration of hydrogen gas from biomass combustion in solid waste incineration NaOH oxides of carbon entrapment model (SWI-NaOH-OCE Model) - Onyelowe, Kennedy C.; A. Onyelowe, Deborah Favour; Bui Van, Duc; Ikpa, Chidozie; Salahudeen, Bunyamin; Eberemu, Adrian O.; Osinubi, Kolawole J.; Onukwugha, Eze; Odumade, Adegboyega O.; Chigbo, Ikechukwu C.; Amadi, Agapitus A.; Igboayaka, Ekene; et al. (Materials Science for Energy Technologies, 2020)
The valorization of biomass-based solid wastes for both geotechnical engineering purposes and energy needs has been reviewed to achieve eco-friendly, eco-efficient and sustainable engineering and reengineering of civil engineering materials and structures. The objective of this work was to review the procedure developed by SWI-NaOH-OCE Model for the valorization of biomass through controlled direct combustion and the sequestration of hydrogen gas for energy needs. The incineration model gave a lead to the sequestration of emissions released during the direct combustion of biomass and the subsequent entrapment of oxides of carbon and the eventual release of abundant hydrogen gas in the entrapment jar. The generation of geomaterials ash for the purpose of soil stabilization, concrete and asphalt modification has encouraged greenhouse emissions but eventually the technology that has been put in place has made it possible to manage and extract these emissions for energy needs. The contribution from researchers has shown that hydrogen sequestration from other sources requires high amount of energy because of the lower energy states of the compounds undergoing thermal decomposition. But this work has presented a more efficient approach to release hydrogen gas, which can easily be extracted and stored to meet the energy needs of the future as fuel cell batteries to power vehicles, mobile devices, robotic systems, etc. More so, the development of MXene as an exfoliated two-dimensional nanosheets with permeability and filtration selectivity properties, which are connected to its chemical composition and structure used in hydrogen gas extraction and separation from its molecular combination, has presented an efficient procedure for the production and management of hydrogen gas for energy purposes.
Keywords: Biomass valorization; Hydrogen gas sequestration; Oxides of carbon entrapment; Geomaterials; Biogas; Hydrogen cell battery; Hydrogen cell fuel